Promoting P450 BM3 heme domain dimerization with a tris(5‐iodoacetamido‐1, 10‐phenanthroline)Ru(II) complex. (26th June 2020) - Kato, Mallory; Foley, Bridget; Vu, Julia; Huynh, Michael; Lucero, Kathreena; Harmon, Caroline; Cheruzel, Lionel
Abstract: Protein dimerization often occurs in many biological systems as to provide structural and functional advantages. A tris(5‐iodoacetamido‐1, 10‐phenanthroline)Ruthenium(II) complex was shown to promote the covalent dimerization of a P450 BM3 heme domain mutant containing a surface‐exposed nonnative single cysteine residue. The formation of homodimeric species was confirmed by protein gel electrophoresis, mass spectrometry and UV–Vis spectroscopy. The dimeric species could be separated from the monomer and aggregates by size‐exclusion chromatography. Docking simulation reveals a plausible structure with two proteins covalently conjugated to the inorganic compound. Abstract : A Ru(II) complex covalently linking two P450 heme domains.